Multi-omics analysis of the dynamic role of STAR+ cells in regulating platinum-based chemotherapy responses and tumor microenvironment in serous ovarian carcinoma - Lan, Hongwei; Yan, Weihua; Huang, Xiao; Cui, Jiali; Hou, Helei (Frontiers in Pharmacology, 2025)
BackgroundSerous ovarian carcinoma (SOC) is the most lethal subtype of ovarian cancer, with chemoresistance to platinum-based chemotherapy remaining a major challenge in improving clinical outcomes. The role of the tumor microenvironment (TME), particularly cancer-associated fibroblasts (CAFs), in modulating chemotherapy responses is not yet fully understood.MethodsTo explore the relationship between CAF subtypes and chemotherapy sensitivity, we employed single-cell RNA sequencing (scRNA-seq), bulk RNA-seq, spatial transcriptomics, immunohistochemistry (IHC), and immunofluorescence (IF). This multi-omics approach enabled the identification, characterization, and functional analysis of CAF subtypes in both chemotherapy-sensitive and chemotherapy-resistant SOC patients.ResultsWe identified steroidogenic acute regulatory protein-positive (STAR+) cells as a novel CAF subtype enriched in chemotherapy-sensitive SOC patients. STAR + cells exhibited unique transcriptional profiles and were functionally enriched in pathways related to P450 drug metabolism, lipid metabolism, and amino acid metabolism, with enhanced pathway activity observed in chemotherapy-sensitive groups. Spatial transcriptomics and IF revealed that STAR + cells were closely localized to tumor cells, suggesting potential cell-cell interactions. Further communication analysis indicated that STAR + cells may suppress WNT signaling in tumor cells, contributing to improved chemotherapy responses. Importantly, STAR expression levels, validated by IHC, were positively correlated with chemotherapy sensitivity and improved patient prognosis. Platinum-based chemotherapy was shown to increase the proportion of STAR + cells, underscoring their dynamic response to treatment.ConclusionOur study identifies STAR + cells as a novel CAF subtype that enhances chemotherapy sensitivity in SOC. By modulating key metabolic pathways and potentially suppressing WNT signaling, STAR + cells could contribute to improved treatment responses. These findings position STAR + cells as a promising biomarker for predicting chemotherapy efficacy in SOC, which warrants further investigation.